2000
DOI: 10.1128/mcb.20.16.5998-6007.2000
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Membrane Trafficking and Actin Remodeling Functions of ARF6 with an Effector Domain Mutant

Abstract: The ADP-ribosylation factor 6 (ARF6) GTPase has a dual function in cells, regulating membrane traffic and organizing cortical actin. ARF6 activation is required for recycling of the endosomal membrane back to the plasma membrane (PM) and also for ruffling at the PM induced by Rac. Additionally, ARF6 at the PM induces the formation of actin-containing protrusions. To identify sequences in ARF6 that are necessary for these distinct functions, we examined the behavior of a chimeric protein of ARF1 and ARF6. The 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 49 publications
7
64
0
1
Order By: Relevance
“…Subcellular localization and physiological function of class II of ARFs are largely unknown. Of three classes of ARF, the class III of ARF, ARF6, localizes at the plasma membrane and is implicated in the regulation of cortical actin dynamics and plasma membrane recycling [19]. In the hippocampus, ARF6 mRNA is expressed in CA1-3 pyramidal cell layers and the dentate gyrus [20].…”
Section: Introductionmentioning
confidence: 99%
“…Subcellular localization and physiological function of class II of ARFs are largely unknown. Of three classes of ARF, the class III of ARF, ARF6, localizes at the plasma membrane and is implicated in the regulation of cortical actin dynamics and plasma membrane recycling [19]. In the hippocampus, ARF6 mRNA is expressed in CA1-3 pyramidal cell layers and the dentate gyrus [20].…”
Section: Introductionmentioning
confidence: 99%
“…6C,D). Arfs 34 constitute a family of Ras-related, low molecular mass ( 20 kDa) GTP-binding proteins that act as molecular switches for membrane and vesicle traffic as well as actin dynamics in cells 35 . In a first step, the interaction of C9ORF72 with these small GTPases was confirmed by co-precipitation analyses, using antibodies against Arf6 (Fig.…”
Section: C9orf72 Depletion Leads To Activation Of Arf6mentioning
confidence: 99%
“…In both arf1-16 and arf1-17 alleles, glutamic acid at position 41 is mutated to valine. Recently, Al-Awar et al (2000) showed that Q37 of mammalian ARF6, corresponding to E41 of yeast Arf1p, is critical for its effector function, formation of protrusion, suggesting that this position represents a site of interaction with effector molecules. arf1-16 has one additional mutation, D129E, which is in the consensus GTP-binding domain, NKXD.…”
Section: Phenotypes Of Arf1 Ts Mutantsmentioning
confidence: 99%